The Ext-3DJPS algorithm for ship path planning in the Arctic - Sun, Youguo; Wu, Da; Ringsberg, Jonas; Lang, Xiao; Mao, Wengang; Zhang, Jinfen (2023)
Safe shipping in the Arctic faces the challenge of complex sea ice environments. To enhance the safety and efficiency of navigation in Arctic waters, we propose an innovative ship path planning algorithm, the Extend Three Dimensional Jump Point Search (Ext-3DJPS), considering navigation safety. The algorithm extends the traditional JPS algorithm to a spatial-risk 3D space. The modified Look Ahead Rules are made to evaluate the risk level of planned paths. Accordingly, a 3D grid risk map is constructed based on the Polar Operational Limit Assessment Risk Indexing System (POLARIS). The proposed algorithm is tested using the 2D-JPS and the original 3D-JPS algorithms. A comparative analysis shows that the paths generated by the 2D-JPS and 3D-JPS algorithms exhibit higher risks than the Ext-3DJPS algorithm. The results demonstrate that the Ext-3DJPS algorithm possesses significant advantages in navigational risk control, making it well-suited for path planning in Arctic shipping.